Пошаговое объяснение:
-8 + 4 = -(8 - 4) = -4
9 + (-3) = 9 - 3 = 6
-14 + (-25) = -14 - 25 = -(14 + 25) = -39
43 + (-31) = 43 - 31 = 12
-6 + (-2) = -6 - 2 = -(6 + 2) = -8
-62 + 31 = -(62 - 31) = -31
-50 + 30 = -(50 - 30) = -20
70 + (-20) = 70 - 20 = 50
1)-8+4= -(8-4)= -4
2)9+(-3)=9-3=6
3)-14+(-25)= -14-25= -(14+25)= -39
4)43+(-31)=43-31=12
5)-6+(-2)= -6-2= -(6+2)= -8
6)-62+31= -(62-31)= -31
7)-50+30= -(50-30)= -20
8)70+(-20)=70-20=50
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Пошаговое объяснение:
-8 + 4 = -(8 - 4) = -4
9 + (-3) = 9 - 3 = 6
-14 + (-25) = -14 - 25 = -(14 + 25) = -39
43 + (-31) = 43 - 31 = 12
-6 + (-2) = -6 - 2 = -(6 + 2) = -8
-62 + 31 = -(62 - 31) = -31
-50 + 30 = -(50 - 30) = -20
70 + (-20) = 70 - 20 = 50
1)-8+4= -(8-4)= -4
2)9+(-3)=9-3=6
3)-14+(-25)= -14-25= -(14+25)= -39
4)43+(-31)=43-31=12
5)-6+(-2)= -6-2= -(6+2)= -8
6)-62+31= -(62-31)= -31
7)-50+30= -(50-30)= -20
8)70+(-20)=70-20=50